2020
DOI: 10.1016/j.pacs.2020.100192
|View full text |Cite
|
Sign up to set email alerts
|

Correction of wavelength-dependent laser fluence in swept-beam spectroscopic photoacoustic imaging with a hand-held probe

Abstract: Recently, we demonstrated an integrated photoacoustic (PA) and ultrasound (PAUS) system using a kHz-rate wavelength-tunable laser and a swept-beam delivery approach. It irradiates a medium using a narrow laser beam swept at high repetition rate (∼1 kHz) over the desired imaging area, in contrast to the conventional PA approach using broad-beam illumination at a low repetition rate (10−50 Hz). Here, we present a method to correct the wavelength-dependent fluence distribution and demonstrate its performance in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…In our previous clinical study on the human calcaneus bone, wavelength-dependent light attenuation was partially addressed based on the bone model [ 25 ]. Previous studies from other groups have also indicated that spectral coloring can be eliminated using model-based or machine-learning-based methods [ [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. Therefore, in future clinical studies, PA absorption curves affected by spectral coloring should be further studied and corrected.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous clinical study on the human calcaneus bone, wavelength-dependent light attenuation was partially addressed based on the bone model [ 25 ]. Previous studies from other groups have also indicated that spectral coloring can be eliminated using model-based or machine-learning-based methods [ [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. Therefore, in future clinical studies, PA absorption curves affected by spectral coloring should be further studied and corrected.…”
Section: Discussionmentioning
confidence: 99%
“…The density of certain tissues or materials also affects the laser absorption in photoacoustic imaging. Chromophores are tissue components that can absorb laser light energy [20]. Several chromophores, such as hydroxyapatite, protein, and blood vessels can be found in oral tissue [21].…”
Section: (A) (B)mentioning
confidence: 99%
“…Kim et al have developed a real-time, spectroscopic PA/US system with simultaneous fluence compensation and motion correction. 149 For PA acquisition, a single image is formed by sequential scanning using a narrow laser beam through fiber sweeping (called “fast-sweep”). Light from different fibers propagates different distances in tissue.…”
Section: Technical Advancements In Molecular Patmentioning
confidence: 99%
“…The procedure is repeated for all wavelengths used in the experiment. Reproduced with permission 149.…”
mentioning
confidence: 99%